Transforming English Learning: The Role of ClassDojo in Enhancing Vocabulary Mastery of International Business Administration Students - Hanik, Siti Rofiatul; Shofiyuddin, Muh (Universitas Negeri Gorontalo, 2025)
The ClassDojo app proved to be effective in improving vocabulary mastery through gamification approaches and interactive features. This approach increased engagement and motivation to learn, created a dynamic and personalized learning environment, and supported more effective language learning. This study examines the effectiveness of ClassDojo in enhancing vocabulary mastery among International Business Administration students. This study was conducted at higher vocational education of Polytechnic Balekambang Jepara, in the International Business Administration department. This research is a quantitative use pretest-posttest design involving 44 fourth-semester students enrolled in the English for Business II course. Results indicated significant improvements in students’ vocabulary mastery post-intervention, as measured through paired-sample t-tests and effect size calculations. ClassDojo’s interactive and gamified approach was shown to increase engagement and motivation, supporting vocabulary acquisition. However, social factors in the classroom also influenced outcomes, suggesting a need for further research to identify unobserved variables affecting vocabulary mastery. These findings highlight the potential of ClassDojo as an effective tool for language learning in higher education.